Pronounced changes in air quality, atmospheric and meteorological parameters, and strong mixing of smoke associated with a dust event over Bakersfield, California - Chauhan, Akshansha; de Azevedo, Samara C. [UNESP]; Singh, Ramesh P. (Springer Nature, 2018)
On September 28, 2016, an intense dust storm impacted the city of Bakersfield and surrounding areas in California. The dust event coincided with smoke aerosols from the forest fire located in the northwest of Bakersfield. In California, forest fires are frequent during summer and fall seasons. The forest fire smoke plumes were subjected to large dispersion and appeared widespread. In this study, we present a detailed analysis of satellite and surface observations indicating pronounced changes in air quality, aerosol characteristics, trace gases, along the prevailing meteorological conditions over Bakersfield associated with the dust event and its interactions with the forest fire smoke. Back trajectory simulations clearly show inflow of the dust airmass from the Mojave Desert located east of Bakersfield, in contrast to the forward trajectories originating from the forest fire event located in the northwestern region, suggesting possibility of mixing of smoke and dust in the Bakersfield area. In addition, low and strong wavelength dependence of aerosol single scattering albedo also supports the observations of strong aerosol mixing of dust and smoke.
Keywords: AERONET; Aerosols; AIRS; AQI; Dust; Forest fire; MODIS; Satellite data